Item Analysis of Academic Procrastination Scale using Classic Test Theory and Item Response Theory among university students - Abdul Rahman Al Shehri (Umm Al-Qura University, 2022)
Aim: The aim of the study was determine item analysis of Procrastination Scale for MclCloskey (2011) in a sample of college students who study statistics course in terms of classical test theory and Item response theory and study the difference between male and female on academic procrastination, determine the levels of academic procrastination. Methodology: The sample consisted of 156 undergraduate 76 (48.7%) and graduate 80 (50.3%) students, sex, male 89 (57.1%) and female 67 (42.9%) who enrolled in some Saudi universities (king khield, king abd- elaziz, hafr elbatan). They answered self-administered scales of Academic Procrastination Scale (APS-SF) and the steel Procrastination scale (2010). Results: A Cronbach's alpha coefficient for academic procrastination scale was 0.945, The exploratory factor analysis shows a four factors, and Graded response two-parameter logistic model for procrastination construct showed appropriate fit with data, difficulty and discrimination indices were estimated for items of scale, the short scale of procrastination consist of 8 items in terms of item analysis criteria of classic test theory and item response theory. Conclusion: The study provided a reliable and valid short version of the Academic Procrastination scale, and it can be useful to quickly diagnosis of academic procrastinating behaviors among the universities students in KSA.